High school math teachers’ perception of math examples and its use for introducing a concept - Ebrāhim Reyhāni; Shahrnāz Bakhshalizādeh; Ahmad Vāsheghāni Farāhāni (فصلنامه نوآوری‌های آموزشی, 2013)
Examples play a significant role at construction and reconstruction of math concepts. Good educational examples like a clear monitor, act as means for connecting learners, teachers and concepts. This study examines math teachers’ perception of examples and how they could be used in the process of teaching a concept. The research method employed in this study was a qualitative survey method. The research population consisted of all high school math teachers of Markazi province in the academic year 89-90 and 75 randomly selected teachers participated as the sample. The results showed that teachers are aware of the necessity of the use of examples, but they do not have sufficient knowledge of educational examples and their example space is not sufficiently developed. Most of the teachers consider examples as useful and necessary tool and as a common understandable language for learners. But it seems that they do not consider theorems, problems, definitions, proofs and reasoning as examples. Teachers pointed out some characteristics for educational examples such as clarity and simplicity, math accuracy, being in accordance with students’ learning ability and being measurable, but a large number of them neglected important characteristics such as generalizability, the availability and richness and power of a math example. Findings also indicated that most of participating teachers used examples in parts of teaching process such as conceptualizing or teaching procedures.